(untitled) (The Pretoria Student Law Review, 2025)
This article critically examines the scope of discretion vested in the Kenya Film Classification Board (KFCB) under the Film and Stage Plays Act in regulating films and stage productions in Kenya. Specifically, the paper questions the absence of a clear standard or test for the determination of what constitutes ‘decency’ or ‘public interest’ in the KFCB’s approval or disapproval of films and posters for public exhibition. Furthermore, the paper evaluates the compatibility of this discretionary power with the constitutional guarantee of artistic freedom of expression under Article 33 of the Kenyan Constitution. Finally, the paper explores the potential impact of KFCB’s discretion on digital rights and digital inclusion in Kenya. By interrogating these issues, this paper seeks to contribute to the ongoing debates on the appropriate balance between regulation and protection of artistic expression, on the one hand, and the realisation of digital rights and digital inclusion, on the other.